Identification and characterization of Aβ peptide interactors in Alzheimer’s disease by structural approaches - Philibert, Keith D.; Marr, Robert A.; Norstrom, Eric M.; Glucksman, Marc J. (Frontiers in Aging Neuroscience, 2014)
Currently, there are very limited pharmaceutical interventions for Alzheimer’s disease (AD) to alleviate the amyloid burden implicated in the pathophysiology of the disease. AD is characterized immunohistologically by the accumulation of senile plaques in the brain with afflicted patients progressively losing short-term memory and, ultimately, cognition. Although significant improvements in clinical diagnosis and care for AD patients have been made, effective treatments for this devastating disease remain elusive. A key component of the amyloid burden of AD comes from accumulation of the amyloid-beta (Aβ) peptide which comes from processing of the amyloid precursor protein (APP) by enzymes termed secretases, leading to production of these toxic Aβ peptides of 40-42 amino acids. New therapeutic approaches for reducing Aβ are warranted after the most logical avenues of inhibiting secretase activity appear less than optimal in ameliorating the progression of AD. Novel therapeutics may be gleaned from proteomics biomarker initiatives to yield detailed molecular interactions of enzymes and their potential substrates. Explicating the APPome by deciphering protein complexes forming in cells is a complementary approach to unveil novel molecular interactions with the amyloidogenic peptide precursor to both understand the biology and develop potential upstream drug targets. Utilizing these strategies we have identified EC3.4.24.15 (EP24.15), a zinc metalloprotease related to neprilysin, with the ability to catabolize Aβ 1-42 by examining first potential in silico docking and then verification by mass spectrometry. In addition, a hormone carrier protein, transthyreitin (TTR), was identified and with its abundance in cerebrospinal fluid, found to clear Aβ by inhibiting formation of oligomeric forms of Aβ peptide. The confluence of complementary strategies may allow new therapeutic avenues as well as biomarkers for AD that will aid in diagnosis, prognosis and treatment.